(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
At the beginning of 21st century, Brazilian Sign Language (LIBRAS) became a mandatory subject for teacher training courses at public and private universities in Brazil. A necessary measure to reduce social inequality between deaf and hearing people. While it is optative for a Graphic Design bachelor degree, the subject of LIBRAS also provides the student with relevant subsidies for the development of projects that aim to make the world more inclusive. This is true for the two Design graduation works that this article presents. By means of an applied exploratory qualitative research, the students developed editorial products for deaf children, in order to expand the possibilities of access to information. In both works, Participatory Design methodology guided data collection and interpretation procedures. The researches resulted in a bilingual illustrated children’s book about the local June festivities and complementary didactic material for the bilingual literacy of children with deafness.